Emotions in “the world”: cultural practices, products, and meanings of anger and shame in two individualist cultures - Boiger, Michael; De Deyne, Simon; Mesquita, Batja (Frontiers in Psychology, 2013)
Three studies tested the idea that people’s cultural worlds are structured in ways that promote and highlight emotions and emotional responses that are beneficial in achieving central goals in their culture. Based on the idea that U.S. Americans strive for competitive individualism, while (Dutch-speaking) Belgians favor a more egalitarian variant of individualism, we predicted that anger and shame, as well as their associated responses, would be beneficial to different extents in these two cultural contexts. A questionnaire study found that cultural practices promote beneficial emotions (anger in the United States, shame in Belgium) and avoid harmful emotions (shame in the United States): Emotional interactions were perceived to occur more or less frequently to the extent that they elicited culturally beneficial or harmful emotions. Similarly, a cultural product analysis showed that popular children’s books from the United States and Belgium tend to portray culturally beneficial emotions more than culturally harmful emotions. Finally, a word association study of the shared cultural meanings surrounding anger and shame provided commensurate evidence at the level of the associated response. In each language network, anger and shame were imbued with meanings that reflected the cultural significance of the emotion: While culturally consistent emotions carried relatively stronger connotations of emotional yielding (e.g., giving in to anger and aggressing against the offender in the United States), culturally inconsistent emotions carried relatively stronger connotations of emotional containment (e.g., a stronger emphasis on controlling anger and moving away from the aggressor in Belgium).